2021
DOI: 10.1155/2021/9918056
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus Disease in Children: A Single-Center Study from Western Saudi Arabia

Abstract: Introduction. Local data in Saudi Arabia regarding pediatric SARS-CoV-2 infection is limited. This study is aimed at adding insight regarding the effect of the novel coronavirus on pediatric patients by studying the presentation, laboratory parameters, and disposition of SARS-CoV-2-infected pediatric patients in one center in Jeddah, Saudi Arabia. Methodology. A retrospective study was conducted at the International Medical Center (IMC) in Jeddah, Saudi Arabia, to assess features of pediatric patients admitted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Multisystem inflammatory syndrome in children (MIS-C) is a unique medical phenomenon that occurs in children 2 to 6 weeks after infection; it develops in less than 0.1% of children with COVID-19 (median age 8.6 years) and requires intensive care support in 68% of cases [ 2 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. One of the first reports on long-term COVID-19 in children was a case report of five Swedish children (median age: 12 years) who had symptoms lasting 6–8 months after acute respiratory infection symptoms [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Multisystem inflammatory syndrome in children (MIS-C) is a unique medical phenomenon that occurs in children 2 to 6 weeks after infection; it develops in less than 0.1% of children with COVID-19 (median age 8.6 years) and requires intensive care support in 68% of cases [ 2 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. One of the first reports on long-term COVID-19 in children was a case report of five Swedish children (median age: 12 years) who had symptoms lasting 6–8 months after acute respiratory infection symptoms [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the Kingdom of Saudi Arabia, studies have shown a dominant benign prognosis of COVID-19 disease in children. A substantial portion were asymptomatic ( Ahmad et al, 2021 ; Almuzaini et al, 2021 ; Hijazi et al, 2021 ) with this rate ranging from 27.9% ( Mosalli et al, 2021 ) to 54.6% ( Alharbi et al, 2021 ). Among symptomatic ones, the most common reported symptoms were fever, cough, runny nose, and shortness of breath ( Harbi et al, 2020 ; Ahmad et al, 2021 ; Alharbi et al, 2021 ; Alshengeti et al, 2021 ; Mosalli et al, 2021 ; Shahin et al, 2021 ; AlGhamdi et al, 2022 ).…”
Section: Childrenmentioning
confidence: 99%
“…A substantial portion were asymptomatic ( Ahmad et al, 2021 ; Almuzaini et al, 2021 ; Hijazi et al, 2021 ) with this rate ranging from 27.9% ( Mosalli et al, 2021 ) to 54.6% ( Alharbi et al, 2021 ). Among symptomatic ones, the most common reported symptoms were fever, cough, runny nose, and shortness of breath ( Harbi et al, 2020 ; Ahmad et al, 2021 ; Alharbi et al, 2021 ; Alshengeti et al, 2021 ; Mosalli et al, 2021 ; Shahin et al, 2021 ; AlGhamdi et al, 2022 ). Gastrointestinal symptoms were also described but to a lesser extent ( Almoosa et al, 2020 ; Alharbi et al, 2021 ; Almuzaini et al, 2021 ; Alnajjar et al, 2021 ; Shahin et al, 2021 ).…”
Section: Childrenmentioning
confidence: 99%
See 2 more Smart Citations